Top management team compensation: the missing link between CEO pay and firm performance? - Carpenter, Mason A.; Sanders, WM. Gerard (Strategic Management Journal, 2002)
Abstract In this research we discuss the relationship between CEO and top management team (TMT) member compensation, and explore the implications of TMT pay for firm performance. Specifically, we suggest that firm performance may benefit due to agency and group behavioral issues when top management team member pay is aligned—alignment is defined as the degree to which TMT member pay reflects (1) shareholder interests and (2) key political and strategic contingencies within the firm. In support of our theorizing, we found CEO pay to be related to TMT pay; TMT compensation, in turn, predicted performance (i.e., return on assets and Tobin's q) when aligned with shareholder interests and internal contingencies. Moreover, the effect of CEO pay on future firm performance was dependent on top team pay. Copyright © 2002 John Wiley & Sons, Ltd.